Nanoscopy of living brain slices with low light levels. - Testa, I; Urban, N; Jakobs, S; Eggeling, C; Willig, K; Hell, S (2012)
Lens-based fluorescence microscopy, which has long been limited in resolution to about 200 nanometers by diffraction, is rapidly evolving into a nanoscale imaging technique. Here, we show that the superresolution fluorescence microscopy called RESOLFT enables comparatively fast and continuous imaging of sensitive, nanosized features in living brain tissue. Using low-intensity illumination to switch photochromic fluorescent proteins reversibly between a fluorescent and a nonfluorescent state, we increased the resolution more than 3-fold over that of confocal microscopy in all dimensions. Dendritic spines located 10-50 μm deep inside living organotypic hippocampal brain slices were recorded for hours without signs of degradation. Using a fast-switching protein increased the imaging speed 50-fold over reported RESOLFT schemes, which in turn enabled the recording of spontaneous and stimulated changes of dendritic actin filaments and spine morphology occurring on time scales from seconds to hours.